Legal Supervision And Enforcement In Environmental Law Under The Law Number 32 Year 2009 On Environmental And Protection Management - Hery Agus Susanto; Daniel Susilo (Yurisdiksi: Jurnal Wacana Hukum dan Sains, 2017)
With La w s upervis ion and enforcement  in Environ mental Law, e le ments  of the environment can be res olved, including elements of cons ervation, s ocial culture and phys ical. Ele ment of conservation (biotic) is ele ment of the environment that cons is ts of a living creature, s uch as a human, anima ls , plants and  mic roorganis ms . Socia l and  Cultura l  Ele ment  is  a s ocial-cu ltural environ ment  created  by  human beings     which     is     a    s ys tem     of     values ,     ideas     and     beliefs     in     behavior     as     s ocial beings. Phys ical Ele ments (abiotic) cons is ts of non-liv ing objects  including  s oil, water, a ir, climate and other elements . The three elements  mus t be maintained  and pres erved from environ mental da mage and pollution. Govern ment is res pons ible for the welfare of his people and has a fundamental res pons ibility in realizing     the    formation     of    environmental     cons ervation.      Protection     and     Management     of law inc ludes Planning, Ut ilization, Ma intenance Controlling, Monitoring and La w En force ment.